Mechanics of Time-Dependent Materials An International Journal Devoted to the Time-Dependent Behaviour of Materials and Structures - Emri, Igor.; Liechti, Ken.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Mechanics of Time-Dependent Materials accepts contributions dealing with the time-dependent mechanical properties of solid polymers, metals, ceramics, concrete, wood, or their composites. It is recognized that certain materials can be in the melt state as function of temperature and/or pressure. Contributions concerned with fundamental issues relating to processing and melt-to-solid transition behaviour are welcome, as are contributions addressing time-dependent failure and fracture phenomena. Manuscripts addressing environmental issues will be considered if they relate to time-dependent mechanical properties. The journal promotes the transfer of knowledge between various disciplines that deal with the properties of time-dependent solid materials but approach these from different angles. Among these disciplines are: Mechanical Engineering, Aerospace Engineering, Chemical Engineering, Rheology, Materials Science, Polymer Physics, Design, and others.
Keywords: Polymers; Mechanics; Materials science; Solid Mechanics; Classical Mechanics; Characterization and Evaluation of Materials; Polymer Sciences